Corporate Social Responsibility and Financial Performance in Commercial Banks of Nepal - Panthi, Top Lal (Patan Prospective Journal, 2023)
In this study, the effect of corporate social responsibility on financial performance proxied by return on assets with a mediating variable size of the banks proxied by number of employees in Nepalese commercial banks, has been examined to fulfill the objective of identifying the size, status and trend of corporate social responsibility and analyzing the effect of CSR with a mediating variable number of employees on return on assets. An aggregate level of CSR with a mediating variable number of employees have been applied as the independent variable and return on assets have undertaken as the dependent variable in the research framework. Panel data sets of ten years from seventeen Nepalese commercial banks have been observed and tested using correlation coefficients and regression analysis under the approach of deductive, descriptive and analytical research design, to analyze the effect of CSR with a mediating variable number of employees of the organization on return on assets. The findings depicts that the increasing trend of CSR expenditure and return on assets have a significant positive relationship. From the analysis, it has concluded that there is a positive relationship between the variables and the impact of CSR on return on assets, symbolizes increasing in CSR leads to an increase in the financial performance of the banks. Furthermore, it raises the public image of the firm and attracts more investors, customers and well-wishers which supports to increase the business and sustainable growth over the competition. This study demands the implication of CSR practices for all the business organization even if not mandatory from the concerned authority.